P624Genetic disruption of the Rac inhibitor ArhGAP15 leads to aortic valve disease in mice. (15th July 2014) - Ghigo, A; Cimino, J; Li, M; Morello, F; Hirsch, E
Abstract: Purpose: The Rac-GTPase activating protein ArhGAP15 negatively modulates the small GTPase Rac in leukocytes. We demonstrated previously that neutrophils lacking ArhGAP15 have enhanced chemotactic responses, straighter directional migration, amplified reactive oxygen specie production and increased bacterial phagocytosis. Given the central role of immune cell activation in cardiac diseases, we intend to investigate the impact of such an hyperactive immune system on cardiac pathophysiology. Methods: Echocardiography was performed to assess heart morphometry and function in 2, 4 and 6 month-old ArhGAP15 WT and KO male mice. Aortic valve structure and inflammation were assessed by H&E staining and immunohistochemistry. Results: Cardiac function and morphometry did not differ significantly between young WT and KO animals (2 months). Conversely, KO mice developed eccentric hypertrophy at 4 months of age as evidenced by a mild increase in heart weight to body weight ratio (HW/BW (mg/g) WT: 3.47±0.14; KO: 4.28±0.22; *P<0.05) and by left ventricle dilation (LVEDD (mm) WT: 3.27±0.17; KO: 3.95±0.11; ***P<0.001). The finding that cardiac output was 45% higher in KO than in WT hearts (CO (ml/min) WT: 12.53±0.47; KO: 21.45±2.29; **P<0.01) indicated that the left ventricle enlargement observed in KO mice was secondary to cardiac volume overload. In keeping with these findings, 40% of KO mice suffered from aortic regurgitation, a major cause of volume overload, and showed aortic valve malformations, including irregular size and thickening of valve leaflets, despite a normal three-leaflet structure. Intriguingly, the structural abnormalities of KO aortic valves were accompanied by enhanced recruitment of inflammatory cells as the number of CD18-positive infiltrating leukocytes was significantly higher than in WT tissues. Aortic valve dysfunction eventually led to systolic failure in aged, 6 month-old KO mice (FS (%) WT: 37.28±1.85; KO: 29.9±0.88; **P<0.01). Conclusion: Altogether, these findings demonstrate that genetic disruption of ArhGAP15 predisposes to cardiac valve disease and predict cardiovascular complications in recently described patients with ArhGAP15 genetic deletions.